2007
DOI: 10.1007/s00330-007-0730-y
|View full text |Cite
|
Sign up to set email alerts
|

Full-field digital mammography compared to screen film mammography in the prevalent round of a population-based screening programme: the Vestfold County Study

Abstract: The purpose of the study was to compare the performance of full-field digital mammography (FFDM) with soft-copy reading to screen film mammography (SFM) used during the first prevalent 2-year round of population-based screening. A total of 18,239 women aged 50-69 years were screened with FFDM as part of the Norwegian Breast Cancer Screening Programme (NBCSP). Process indicators were compared to data from 324,763 women screened with SFM using the common national database of the NBCSP. The cancer detection rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
79
3
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 29 publications
6
79
3
4
Order By: Relevance
“…Use of CAD could lead to more sensitive detection of micro-calcifications by Karssemeijer et al [18] . The fact that previous studies [5,6] without CAD also reported increased detection of micro-calcifications, suggest that this result should not be attributed to CAD alone. Another factor may be the distribution of patients between the first screening round and subsequent rounds.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…Use of CAD could lead to more sensitive detection of micro-calcifications by Karssemeijer et al [18] . The fact that previous studies [5,6] without CAD also reported increased detection of micro-calcifications, suggest that this result should not be attributed to CAD alone. Another factor may be the distribution of patients between the first screening round and subsequent rounds.…”
Section: Discussionmentioning
confidence: 52%
“…Oslo 2 study [4] , showed significantly higher cancer detection rate with FFDM in women between 45 and 69 years of age (5.9 versus 3.8 per 1000 (p = 0.002). Studies [5,6,8,17] done in the context of routine screening mammograms showed similar results. Del Turco et al [5] and Vigeland et al [6] compared SFM and FFDM in a local population based programme and found statistically higher detection rate for FFDM, which was marked for cancers presenting with microcalcification.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations